The Implementation of Grammarly Application as a Tool to Improve Students’ Writing Ability - Ovi Syapitri; Herlina Herlina; Hermansyah Hermansyah (Jurnal Pendidikan Bahasa, 2023)
This study aims to apply the use of the Grammarly Application in improving students' writing ability. This study uses a Quasi-Experimental design. This research was conducted at MTs Fajar Siddiq Palembang. There were two groups selected by purposive sampling, consisting of VII.2 grade as the experiment group and VII.3 grade as the control group. Each student was given a pre-test at the beginning of the study and a post-test at the end of the study. Data processing in this study using the Independent sample t-test. This study results that students who are given an application of the Grammarly Application can help students in reducing errors in writing significantly, as evidenced by the results of the pre-test and post-test data that have been given. The Grammarly Application has proven to be more effective at helping to reduce errors in writing such as grammar, spelling, and punctuation. This research can be a suggestion for teachers as an alternative to student writing that supports students' independent learning environment.